Transformasi Pendidikan di Indonesia: Peran Indeks Pembangunan Manusia, Akses Internet, dan Pengeluaran Pemerintah untuk Pendidikan - Azmi Nuhisa; Puty Andini; Safuridar Safuridar (Universitas 45 Surabaya, 2025)
This study examines the influence of the Human Development Index (HDI), internet access, and government expenditure on education on the average years of schooling in Indonesia from 2009 to 2024. Employing a quantitative approach using multiple linear regression and secondary data from Statistics Indonesia (BPS), the research aims to clarify how human development quality, digital expansion, and fiscal commitment interact to shape national educational outcomes. The findings reveal that HDI and internet access exert a positive and significant impact on the increase in average years of schooling, underscoring the essential roles of human capital quality and equitable digital infrastructure in driving educational transformation. Conversely, government spending on education shows a negative and significant effect, suggesting potential inefficiencies in budget allocation or the long-term nature of educational investments. The model demonstrates exceptionally strong predictive power with an R² value of 99.57%. These results highlight the need to enhance the efficiency of education spending, accelerate the equal distribution of internet access, and strengthen human development synergy to ensure sustainable improvements in educational quality.